2020
DOI: 10.3390/biomedicines8090349
|View full text |Cite
|
Sign up to set email alerts
|

Lung Microbiome Differentially Impacts Survival of Patients with Non-Small Cell Lung Cancer Depending on Tumor Stroma Phenotype

Abstract: The link between a lung tumor and the lung microbiome is a largely unexplored issue. To investigate the relationship between a lung microbiome and the phenotype of an inflammatory stromal infiltrate, we studied a cohort of 89 patients with non-small cell lung cancer. The microbiome was analyzed in tumor and adjacent normal tissue by 16S rRNA amplicon sequencing. Characterization of the tumor stroma was done using immunohistochemistry. We demonstrated that the bacterial load was higher in adjacent normal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
(45 reference statements)
1
21
0
2
Order By: Relevance
“…Necrotic areas were ignored. The content of CD68, PU.1, CD163, CD3, CD8, FoxP3, CD20, CD56 and CD66b in tumor stroma was expressed as the median of the cell number in one microscopic field [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Necrotic areas were ignored. The content of CD68, PU.1, CD163, CD3, CD8, FoxP3, CD20, CD56 and CD66b in tumor stroma was expressed as the median of the cell number in one microscopic field [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Samples with scores 0–1 for CD206, CD8, and FoxP3 were combined in a group with low expression and samples with scores 2–3 were combined in a group with high expression. For CD68, CD163, CHID1, and CD3, samples with scores 0, 1, and 2 were combined in a group with low expression and samples with a score of 3 represented a group with high expression [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are also existing microbes in cancer tumors [9], and the microbes in cancer tissues are very different from those in non-tumor tissues [10,11]. Many studies have con rmed that there are many microbes in the lung tissue [12][13][14][15]. Existing studies have shown that gut microbes can affect the composition of lung microbes through gut-lung axis, thereby affecting the development of LC [16].…”
Section: Introductionmentioning
confidence: 99%